Healthy Living Lifestyles: Land and Sea - Razieh Farzad; Brittany Scharf; Jim E. Davis; LuAnn Duncan; Jana Anderson (EDIS)
This new 5-page publication of the UF/IFAS Food Science and Human Nutrition Department provides information for the general public about the benefits of incorporating land- and water-based natural resource activities to achieve a healthy lifestyle. Written by Razieh Farzad, Brittany Scharf, Jim E. Davis, LuAnn Duncan, and Jana Anderson. https://edis.ifas.ufl.edu/fs441